Dinamika Regulasi BMT: Dari Konkordansi Menuju Unifikasi Hukum Berdasarkan UU P2SK No 4 Tahun 2023 - Fauzia Ulirrahmi; Nur Sholichin; Kholis Hayatuddin; M. Zumar Aminuddin; Masjupri Masjupri; Rial Fuadi; Mansur Efendi; Nurul Huda (IAIN Langsa, 2026)
This study aims to analyze the regulatory dynamics of Baytul Māl wat Tamwīl (BMT) within the Indonesian legal system, particularly the shift from regulatory fragmentation to legal unification following the enactment of Law Number 4 of 2023 on Financial Sector Development and Strengthening (UU P2SK), as well as its institutional implications for BMT. This research employs a normative legal method using historical, statutory, and conceptual approaches. The findings indicate that prior to UU P2SK, the legal construction of BMT was shaped by the legacy of the concordance principle, which relied on legal entity classification and resulted in fragmented regulation. As a consequence, BMT developed strong social legitimacy at the grassroots level but lacked a solid juridical foundation. Following the enactment of UU P2SK, BMT has been formally recognized as part of the national financial ecosystem, with a regulatory framework based on functional roles and risk exposure through open-loop and closed-loop schemes. This unification has ended regulatory fragmentation, resolved supervisory dualism, and directed BMT toward more accountable governance standards. However, BMT remains vulnerable to identity erosion due to the dominance of tamwīl (commercial) logic, shifting its orientation from community empowerment toward profit and financial stability. The main challenge in the post-P2SK era lies in BMT’s ability to maintain a balance between its māl and tamwīl functions while preserving its foundational ethos and ideological orientation amid increasing demands for professionalism and regulatory compliance.